Bubble Formation Characteristic of Submerged Single-Hole Orifice in Aerosol Suspension - Sun, Qingyang; Gu, Haifeng; Yu, Xiang; Yin, Weikai (Frontiers in Energy Research, 2019)
Bubble column is regarded as an effective containment filtration method. A large amount of radioactive aerosol will retain in liquid pool and generate decay heat. And the surface tension, viscosity and other parameters of liquid phase are affected by increasing of the temperature of liquid pool and the presence of aerosol in pool, which in turn affects the formation characteristics of bubbles. Another important factor affecting bubble generation characteristics is the proportion of steam in gas phase, that is, the exchange of mass and energy of gas phase. This paper will investigate the effects of liquid temperature, aerosol and gas phase composition on bubble formation characteristics by analyzing the variation of bubble detachment volume of the orifice in liquid pool.